Peran Pemerintah dan Masyarakat dalam Upaya Pengembangan Pendidikan Nonformal (Studi Kasus: Eksistensi "Kampung Inggris" Kabupaten Kediri) - Heningtyas, Murdiana Asih (Jurnal Administrasi Publik, 2014)
Abstract: Role of enment and Community Development Efforts in Nonformal Education (Case Study: The existence of "Kampung Inggris" district of Kediri). Nonformal education as part of the educational system have the same duties with other education namely, providing the best service to the community. The procurement of nonformal education activities tend to be more organised by community supported by the Government. This research highlights the role of Government and the community in an effort the development of nonformal education in the Kampung Inggris, Kediri District. Kampung Inggris is a region consisting of 131 Institute courses, as the application of the nonformal education. The fact that more people play an active role in the implementation of the provision of educational services in the Kampung Inggris. Besides communities facilitate migrants by providing a wide range of needs, such as making the business opportunities for the local community that can improve the economy. The role of Government more into a driving force of the roles that society has been implemented. Keywords: Nonformal Education, Kampung Inggris, government, community Abstrak: Peran Pemerintah dn Masyarakat Dalam Upaya Pengembangan Pendidikan Nonformal (Studi Kasus: Eksistensi â€œKampung Inggrisâ€ Kabupaten Kediri). Pendidikan Nonformal sebagai bagian dari sistem pendidikan memiliki tugas sama dengan pendidikan lainnya yakni memberikan pelayanan terbaik terhadap masyarakat. Pengadaan kegiatan pendidikan nonformal cenderung lebih diadakan oleh masyarakat dengan didukung oleh pemerintah. Penelitian ini menyoroti peran pemerintah dan masyarakat dalam upaya pengembangan pendidikan nonformal di Kampung Inggris, Kabupaten Kediri. Kampung Inggris merupakan wilayah yang terdiri dari 131 lembaga kursus, sebagai penerapan dari jalur pendidikan nonformal. Faktanya masyarakat lebih berperan aktif dalam pelaksanaan penyediaan pelayanan pendidikan di Kampung Inggris. Selain itu masyarakat memfasilitasi para pendatang dengan menyediakan berbagai kebutuhan, hal tersebut sekaligus menjadikan peluang usaha bagi masyarakat sekitar yang dapat meningkatkan taraf ekonominya. Peran pemerintah lebih menjadi pendorong dari peran yang telah dilaksanakan masyarakat. Kata kunci: Kampung Inggris, pendidikan nonformal, pemerintah, masyarakat Abstract: Role of Government and Community Development Efforts in Nonformal Education (Case Study: The existence of "Kampung Inggris" district of Kediri). Nonformal education as part of the educational system have the same duties with other education namely, providing the best service to the community. The procurement of non-formal education activities tend to be more organised by community supported by the Government. This research highlights the role of Government and the community in an effort the development of non-formal education in the Kampung Inggris, Kediri District. Kampung Inggris is a region consisting of 131 Institute courses, as the application of the non-formal education. The fact that more people play an active role in the implementation of the provision of educational services in the Kampung Inggris. Besides communities facilitate migrants by providing a wide range of needs, such as making the business opportunities for the local community that can improve the economy. The role of Government more into a driving force of the roles that society has been implemented. Keywords: non-formal Education, Kampung Inggris, Government, Community